2016
DOI: 10.1007/s11104-016-2828-y
|View full text |Cite
|
Sign up to set email alerts
|

Root quality and decomposition environment, but not tree species richness, drive root decomposition in tropical forests

Abstract: Background and aims Tropical forests contribute significantly to the global carbon cycle, yet the relative importance of tree diversity on key ecosystem processes such as root decomposition remains unknown.Methods We examined the influence of tree species richness on root decomposition over 485 days at two sites in Panama with contrasting soil fertility. Diversity effects on decomposition rates were calculated where 1) overstory tree species richness and composition matched that occurring inside root decomposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 85 publications
4
12
0
Order By: Relevance
“…These litter identity effects mostly were interpreted based on few, commonly measured traits such nitrogen (N), C and lignin concentrations (Adair et al., 2008; Hättenschwiler & Jørgensen, 2010), which have been assumed to exert the strongest control on litter decomposition rates. However, there is increasing evidence that other litter traits regulating decomposer and enzyme activities, including concentrations of plant secondary compounds as well as micronutrients such as calcium (Ca), magnesium (Mg) and manganese (Mn), can be more important in driving litter decomposition than the more commonly used nutrient and C quality traits (Berg et al., 2017; Berg, Steffen, & McClaugherty, 2007; García‐Palacios, McKie, Handa, Frainer, & Hattenschwiler, 2016; Guerrero‐Ramírez et al., 2016; Makkonen et al., 2012; Pérez‐Harguindeguy et al., 2000; Vaieretti, Harguindeguy, Gurvich, Cingolani, & Cabido, 2005). Therefore, to better understand the underlying drivers of litter identity effects on decomposition, and how they interact with climate at large spatial scales and across biomes, decomposition studies should assess a large number of leaf litter traits, including those that, like micronutrients, are not commonly considered.…”
Section: Introductionmentioning
confidence: 99%
“…These litter identity effects mostly were interpreted based on few, commonly measured traits such nitrogen (N), C and lignin concentrations (Adair et al., 2008; Hättenschwiler & Jørgensen, 2010), which have been assumed to exert the strongest control on litter decomposition rates. However, there is increasing evidence that other litter traits regulating decomposer and enzyme activities, including concentrations of plant secondary compounds as well as micronutrients such as calcium (Ca), magnesium (Mg) and manganese (Mn), can be more important in driving litter decomposition than the more commonly used nutrient and C quality traits (Berg et al., 2017; Berg, Steffen, & McClaugherty, 2007; García‐Palacios, McKie, Handa, Frainer, & Hattenschwiler, 2016; Guerrero‐Ramírez et al., 2016; Makkonen et al., 2012; Pérez‐Harguindeguy et al., 2000; Vaieretti, Harguindeguy, Gurvich, Cingolani, & Cabido, 2005). Therefore, to better understand the underlying drivers of litter identity effects on decomposition, and how they interact with climate at large spatial scales and across biomes, decomposition studies should assess a large number of leaf litter traits, including those that, like micronutrients, are not commonly considered.…”
Section: Introductionmentioning
confidence: 99%
“…For example, root decomposition has been reported to be negatively (Hobbie et al ., 2010) or not (Sun et al ., 2018) correlated with root diameter. In addition, studies have reported positive (Guerrero‐Ramírez et al ., 2016; Prieto et al ., 2016) or negative (Hobbie et al ., 2010; Jo et al ., 2016) relationships between root decomposition and specific root length (SRL). Such discrepancies could be attributed to the arbitrary definition of fine roots based on a diameter threshold of 2 mm (Pregitzer et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in humid tropical forests, decomposition of leaf litter on the forest floor is rapid (<3 years) (11), and a large proportion of surface litter is likely respired back to the atmosphere as CO 2 rather than transported downward and stored in mineral soils. Root C, in contrast, is transferred directly into mineral soils, where tough, lignin-rich tissues, saturated conditions, and low oxygen levels can slow decomposition, leading to greater C retention of root tissues relative to leaf litter (12,13). Thus, estimates of root biomass, rather than aboveground C stocks, are likely to be more useful for predicting tropical soil C stocks.…”
Section: Introductionmentioning
confidence: 99%